The Effect of Ice Cubes Sipping on Reducing Thirst Among Hemodialysis Patients - Anggraeni, Risma; Putri, Tri Antika Rizki Kusuma; Agustiyowati, Tri Hapsari Retno (STIKep PPNI Jawa Barat, 2023)
Aims: Patients with chronic kidney disease undergoing hemodialysis must limit fluids to prevent fluid overload, which worsens the condition of patients with chronic kidney disease. Restricting fluids results in reduced oral intake, which results in a dry mouth and rarely flowing water on the tongue. This condition can trigger a feeling of thirst. One way to manage thirst is to chew ice cubes. Objective: to determine the effect of chewing ice cubes on reducing thirst in patients undergoing hemodialysis. Method: This research is a type of quantitative research with Quasy Experiment research with a pretest and posttest approach with a sample size of 60 respondents, 30 respondents in the intervention group, and 30 respondents in the control group using purposive techniques sampling. And for data collection using the DTI (Dialysis) questionnaire Thirst Inventory). Results: The effect of giving the intervention of chewing ice cubes to patients undergoing hemodialysis obtained a p-value of 0.000 (p < 0.05) for pre-post in the intervention group and a p-value of 0.317 (p > 0.05) for pre-post in the control group. It can be concluded that the posttest value of the intervention group and the posttest value of the control group obtained a p-value of 0.000 (< 0.05). It can be concluded that there is a significant difference in group posttest scores between the intervention group and the control group. Conclusion: The results of the study show that the intervention of chewing ice cubes in patients with chronic kidney disease has an effect so that it can be used.